Eletrorrecuperação de cobre em rota proposta para a recuperação de metais no contexto da mineração urbana - Tamíris Roxana da Silva (2020)
In this work the effects of operational variables (temperature and current density) and electrolyte composition (copper concentration, acidity and the presence of impurities - zinc ions, Zn2+, and hydrogen peroxide, H2O2) on the copper electrowinning were evaluated. Synthetic solutions and liquor from the printed circuit boards (PCB) connector pins leaching process were used. The approach involved conducting electrowinning tests, electrochemical measurements, physical-chemical and chemical analysis of electrolytes and characterization of Cu deposits by using XRD and SEM-EDS analysis. In the tests performed with synthetic solution, only temperature had a significant impact (up to 4% increases) on the specific energy consumption (SEC) of the electrowinning process. All current efficiency (CE) measured were about 100%. There was no relevant impact on CE in the presence of Zn2+ ions. However, there was an increase in SEC with remarkable effect at 75 g L-1. At this concentration level and at 250 A m-2, the increase in the SEC was around 4%. Regarding the morphology of the copper deposits, the combined effect of high zinc concentrations and current density at 450 A m-2 resulted in the formation of nodular deposits. Studies on the effects on copper recovery under the possible presence of residual H2O2 in the sulfate liquor revealed that this species is extremely harmful to the process, reducing CE up to 70% at the concentration of 1.75 g L-1 (possibly by promoting secondary cathodic reactions). Consequently, there was a significant impact on the SEC. Regarding to the direct feeding of the leaching liquor in the electrowinning cell, the results were very promising. It was shown that it is possible to recover copper with high productivity level. The use of the Dimensionally Stable Anode was effective in reducing cell voltage and SEC as a consequence. In addition, the deposits produced can be smooth and with purity of at least 99.9% by operating the process at 35 ° C, 250 A m-2 and keeping at low levels the concentrations of harmful impurities. Therefore, the study carried out has brought important contributions to the development of a hydro and electro-metallurgical route in the context of urban mining.